The role of material deprivation and consumerism in the decisions to engage in transactional sex among young people in the urban slums of Blantyre, Malawi. Issue 3 (15th March 2016) - Kamndaya, Mphatso; Vearey, Jo; Thomas, Liz; Kabiru, Caroline W.; Kazembe, Lawrence N.
Abstract : Transactional sex has been associated with a high risk of HIV acquisition and unintended pregnancy among young women in urban slums in sub-Saharan Africa. However, few studies have explored the structural drivers of transactional sex from the perspective of both genders in these settings. This paper explores how young men and women understand the factors that lead to transactional sex among their peers, and how deprivation of material resources (housing, food and health care access) and consumerism (a desire for fashionable goods) may instigate transactional sex in the urban slums of Blantyre, Malawi. Data from 5 focus group discussions and 12 in-depth interviews undertaken with a total of 60 young men and women aged 18–23 years old, conducted between December 2012 and May 2013, were analysed using anticipated and grounded codes. Housing and food deprivation influenced decisions to engage in transactional sex for both young men and women. Poor health care access and a desire for fashionable goods (such as the latest hair or clothing styles and cellular phones) influenced the decisions of young women that led to transactional sex. Interventions that engage with deprivations and consumerism are essential to reducing sexual and reproductive health risks in urban slums.